2022
DOI: 10.1111/njb.03611
|View full text |Cite
|
Sign up to set email alerts
|

Hemiboea shimentaiensis S. Y. Miao, Y. Q. Li & T. Chen (Gesneriaceae), a new species from northern Guangdong, China

Abstract: Hemiboea shimentaiensis (Gesneriaceae), a new species from northern Guangdong, China, is described and illustrated. It is most similar to H. gamosepala, H. rubribracteata and H. malipoensis in the nearly white corolla, which appears in a few species of Hemiboea, and nearly glabrous inner base of the corolla tube. It can be easily distinguished from the latter three species by the stoloniferous habit, distinct silvery veins, glabrous corolla except for a ring of hairs inside, anther coherent along ventral face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…To date, over 100 KRTAPs have been identified in mammals across a range (Gong et al, 2010;Khan et al, 2014;Gong et al, 2016), and 88 functional KRTAPs have been reported in human species (Rogers and Schweizer, 2005;Rogers et al, 2007;Rogers et al, 2008). Li studied Chinese Merino and Small-tail Han sheep, mohair Angora goats and cashmere goat and identified 173 proteins in sheep and goats (Li et al, 2018). We found that KRT and KRTAP accounted for the majority of detectable proteins in hair fibers by proteomic analysis.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…To date, over 100 KRTAPs have been identified in mammals across a range (Gong et al, 2010;Khan et al, 2014;Gong et al, 2016), and 88 functional KRTAPs have been reported in human species (Rogers and Schweizer, 2005;Rogers et al, 2007;Rogers et al, 2008). Li studied Chinese Merino and Small-tail Han sheep, mohair Angora goats and cashmere goat and identified 173 proteins in sheep and goats (Li et al, 2018). We found that KRT and KRTAP accounted for the majority of detectable proteins in hair fibers by proteomic analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Accumulated historical demand and artificial selection of specific fiber types lead to the diversity of fleece types. For this reason, we attempted to form a comprehensive view of proteins involved in the composition of selected animal fibers (Li et al, 2018). To separate fiber proteins that are associated with fleece type, in this work, we performed traits and proteome-wide analysis of hair fibers with changed phenotypes in sheep and goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pairing with conductive materials has been verified as one of the most effective approaches. [ 47–49 ] Herein, to appropriately adapt the ion/electron transport and thus promote the utilization potentials for electrochemical storage devices, 2D/2D SSG heterostructures were designed by coupling 2D graphene with the as‐synthesized 2D SSN unit. It is expected that the electrical conductivity can be significantly improved, the active channels can be enlarged within the heterostructured interfaces, and the mechanical robustness can be reinforced, which are desired properties for free‐standing membrane electrodes, thus resulting in excellent electrochemical Li‐/Na‐ion storage performances for LIBs and SIBs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] Unlike the heredity of CN, CO, and CC/CC from the PDA‐derived carbon, the presence of CSe is attributed to the atomic doping in carbon shell during the selenization process, which is further proved by the existence of SeC bond in Se 3d at 57.5 eV (Figure 3e). [ 17 ] As for the N 1s spectrum (Figure 3f), three deconvoluted peaks at 403.7, 400.5, and 398.4 eV are assigned to N‐Q (graphitic‐N), N‐5 (pyrrolic‐N), and N‐6 (pyridinic‐N), respectively. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%